A role of friction-induced torque in sliding friction of rubber materials. (January 2016) - Maegawa, Satoru; Itoigawa, Fumihiro; Nakamura, Takashi
Abstract: Herein, the role of friction-induced torque in sliding friction of rubber materials is investigated. A friction tester was developed to monitor the friction force between a silicon rubber block and a surface made of PMMA 1 . Based on the experimental results, a simplified model was developed to express the nonuniform distribution of normal pressure developed due to the friction-induced torque, and the normal pressure dependence of the real contact area based on Persson׳s contact theory. Based on the modeling, the mechanism of the effect of the friction-induced torque on frictional force reductions was clarified. Highlights: A role of friction-induced torque in sliding friction of rubber materials was discussed. A friction tester was developed to monitor the friction force between a silicon rubber block and PMMA plate. The contact interface between PDMS/PMMA was directly observed using a total reflection optical system. A simplified model that can express the effect of friction-induced torque on friction force was developed.